Production, characterization and water filtration performance of polyvinylidene fluoride-based membranes performance of polyvinylidene fluoride membranes - Arat, Seren Acarer; Pir, Inci; Tufekci, Mertol; Tufekci, Nese (Informa UK Limited, 2025)
PVDF, PVDF/PVP and PVDF/PVP/CNC membranes were prepared using the phase inversion method using polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP) and cellulose nanocrystal (CNC). The morphologies of the membranes and CNC were determined by scanning electron microscopy (SEM), and the mechanical properties of the membranes were determined by tensile tests. After lake water filtration, the fouled membranes were subjected to physical cleaning for 15 min, and then pure water fluxes of fouled-cleaned membranes were determined. The antifouling abilities of the membranes were investigated by calculating the total fouling ratio (Rt), reversible fouling ratio (Rr), irreversible fouling ratio (Rir), and flux recovery ratio (FRR) of the membranes. Moreover, antifouling abilities were further investigated by SEM. With the addition of 6 wt% PVP to 12 wt% PVDF-based membrane, the water content, pure water flux, elastic modulus and tensile strength of the membrane decreased by 25.5%, 16.6%, 34.3% and 31.3%, respectively. As a result of 0.5 wt% CNC reinforcement of PVDF/PVP, pure water flux, water content, elasticity modulus, tensile strength and FRR value of the membrane increased by 5%, 5.5%, 17.6%, 5.8% and 3%, respectively. The turbidity and electrical conductivity removal efficiencies of the membranes from lake water ranged between 38.22-74.76% and 19.32-34.62%, respectively.
Keywords: Antifouling ability; characterization; cellulose nanocrystal; polyvinylpyrrolidone; membrane